Mononuclear and One‐Dimensional Cobalt(II) Complexes with the 3, 6‐Bis(picolylamino)‐1, 2, 4, 5‐tetrazine Ligand. Issue 3 (18th December 2017) - Stetsiuk, Oleh; El‐Ghayoury, Abdelkrim; Lloret, Francesc; Julve, Miguel; Avarvari, Narcis
Abstract : We describe herein the synthesis and structural characterization of a tetrazine‐based bis(picolylamine) ligand, namely, N 3, N 6 ‐bis(pyridin‐2‐ylmethyl)‐1, 2, 4, 5‐tetrazine‐3, 6‐diamine (L, 1 ), which was prepared by the direct reaction between 2 equiv. of picolylamine and 3, 6‐dichloro‐1, 2, 4, 5‐tetrazine. Its reaction with cobalt(II) hexafluoroacetylacetonate hydrate afforded the mononuclear complex [Co(hfac)2 L]· CH3 CN (2, Hhfac = hexafluoroacetylacetone) and the chain compound {[Co(hfac)2 (µ‐L)][Co(hfac)2 (CH3 OH)2 ]} n (3 ). The crystal structures of1 –3 were determined by X‐ray structure analysis. The metal centre in2 is trischelated by two hfac ligands and one picolylamine unit. The two crystallographically independent cobalt(II) ions in3 (Co1 and Co2) are six‐coordinate. Two bidentate hfac groups in equatorial positions and two trans ‐positioned pyridine nitrogen atoms build the coordination polyhedron around Co1 to form a neutral zigzag chain compound, which cocrystallizes with the mononuclear species trans ‐[Co2 (hfac)2 (CH3 OH)2 ]. The magnetic properties of2 and3 were investigated in the temperature range 1.9–300 K. The decrease of the χ M T values of2 and3 upon cooling is mainly due to the depopulation of the higher energy Kramers doublets of the magnetically isolated six‐coordinate cobalt(II) ions. Alternating‐current (ac) magnetic susceptibility measurements of2 and3 revealed the occurrence of frequency‐dependent out‐of‐phase signals under applied direct‐current (dc) fields at very low temperatures, and this result is indicative of single‐ion magnet (SIM) behaviour. Abstract : The 3, 6‐bis(picolylamine)‐1, 2, 4, 5‐tetrazine ligand provides mononuclear and one‐dimensional polymer chain cobalt(II) complexes that show magnetic properties indicative of single‐ion magnet (SIM) behavior.